2020
DOI: 10.1002/ece3.7128
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee identification and social network construction through an online citizen science platform

Abstract: Citizen science has grown rapidly in popularity in recent years due to its potential to educate and engage the public while providing a means to address a myriad of scientific questions. However, the rise in popularity of citizen science has also been accompanied by concerns about the quality of data emerging from citizen science research projects. We assessed data quality in the online citizen scientist platform Chimp&See, which hosts camera trap videos of chimpanzees (Pan troglodytes) and other species acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…However, since the study was conducted when few juvenile animals were present and most male deer still had their antlers making them easier to recognize, further analyses across seasons are needed to determine more precisely the ability of citizen scientist to identify age and sex of animals accurately from photo and video footage. It is likely that more citizen science projects will start requiring human observers to move beyond species classifications; provision of additional detail is already evident in projects asking participants to identify age and sex (Thel et al., 2021) and individual ID (McCarthy et al., 2021; Tagg et al., 2018). Further research is needed to establish optimum camera settings for accurate identification of these traits, although video appears to offer clear benefits over traditional photos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the study was conducted when few juvenile animals were present and most male deer still had their antlers making them easier to recognize, further analyses across seasons are needed to determine more precisely the ability of citizen scientist to identify age and sex of animals accurately from photo and video footage. It is likely that more citizen science projects will start requiring human observers to move beyond species classifications; provision of additional detail is already evident in projects asking participants to identify age and sex (Thel et al., 2021) and individual ID (McCarthy et al., 2021; Tagg et al., 2018). Further research is needed to establish optimum camera settings for accurate identification of these traits, although video appears to offer clear benefits over traditional photos.…”
Section: Discussionmentioning
confidence: 99%
“…Camera trap videos could allow for easier species identification because movement can make animals easier to locate within the footage, and because more information is available to an observer, such as different views of an animal, their gait or movement profile, and sound. However, probably owing to the concerns outlined above, most camera trap citizen science projects use photographs and there has been little assessment of citizen science classification accuracy of videos (but see McCarthy et al., 2021). Gaining adequate numbers of classifications is important for timely processing and for combining multiple classifications to achieve higher confidence in classification accuracy (Anton et al., 2018; Egna et al., 2020; Hsing et al., 2018; Swanson et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations overlap with best practices advised for citizen-science projects to produce reliable results [78]. Previous studies have shown that citizen-science volunteers can produce high accuracy results, performing classifications comparable to professional scientists [79][80][81], and even detect novel features in data [82][83][84]; here, we have shown volunteers can go beyond this, and identify new classes analogously to experts. When provided with suitable resources, citizen-science volunteers can make significant scientific discoveries based upon complex data sets.…”
Section: Discussionmentioning
confidence: 55%
“…These recommendations overlap with best practices advised for citizen-science projects to produce reliable results [65]. Previous studies have shown that citizen-science volunteers can produce high accuracy results, performing classifications comparable to professional scientists [66][67][68], and even detect novel features in data [69][70][71]; here, we have shown volunteers can go beyond this, and identify new classes analogously to experts. When provided with suitable resources, citizen-science volunteers can make significant scientific discoveries based upon complex data sets.…”
Section: Discussionmentioning
confidence: 59%